The Roles of Parental Support and Family Stress in Adolescent Sleep. Issue 5 (4th August 2017) - Tsai, Kim M.; Dahl, Ronald E.; Irwin, Michael R.; Bower, Julienne E.; McCreath, Heather; Seeman, Teresa E.; Almeida, David M.; Fuligni, Andrew J.
Abstract : The current study examines the association between parental support and adolescent sleep under varying levels of family stress. Participants included 316 adolescents ( M age  = 16.40 years, 43% male) and their parents ( M age  = 45.67 years, 91% mothers) from diverse ethnic backgrounds. Both adolescents and parents completed questionnaires and adolescents wore wrist actigraphs and completed self‐reports on their sleep for 7 consecutive days. Results indicated that under contexts of family stress, more parental support was linked to longer sleep duration, less sleep variability, and less time spent awake during the night. Findings suggest that under contexts of family stress, cohesive family relationships may provide a sense of stability and security that is necessary for healthful sleep.